Glycerol as feedstock in the synthesis of chemicals: a life cycle analysis for acrolein production. Issue 1 (19th September 2014) - Cespi, D.; Passarini, F.; Mastragostino, G.; Vassura, I.; Larocca, S.; Iaconi, A.; Chieregato, A.; Dubois, J.-L.; Cavani, F.
Abstract : Three synthetic routes to obtain acrolein are compared, from a life cycle point of view: one by propylene oxidation and two by the dehydration of glycerol, obtained as a co-product either in triglyceride transesterification to FAME or in hydrolysis to fatty acids. Abstract : Glycerol is an important bio-platform molecule, potentially usable for the synthesis of various chemicals and fuel additives, the synthesis of acrolein by dehydration being one of the most studied reactions. Through the application of the life cycle assessment (LCA) methodology we investigated the production of acrolein from glycerol, by comparing two alternative scenarios in which glycerol is obtained as a co-product either in triglyceride trans-esterification to FAME or in hydrolysis to fatty acids. Our results show how the main impacts are not related to the energy involved in the two processes. In fact, the use of dedicated crops as a source of triglycerides in the biodiesel production entailed higher impacts in terms of land exploitation. On the other hand, beef tallow was assumed as a starting raw material in the production of fatty acids, and this involved some significant impacts associated with animal rearing. At the same time, however, avoiding the use of dedicated biomass ensured a lower global impact (in terms of single scores). Lastly, in order to validate the model created, a sensitivity analysis using the Monte Carlo method was performed. The two routes from glycerol were also compared with the classical chemical route where acrolein is produced by propylene oxidation.